You Don't Always Get What You Want: The Effect of Financial Incentives on State Fiscal Health. (27th February 2020) - McDonald, Bruce D.; Decker, J. W.; Johnson, Brad A. M.
Abstract: Governments frequently use financial incentives to encourage the creation, expansion, or relocation of businesses within their borders. Research on financial incentives gives little clarity as to what impact these incentives may have on governments. While incentives may draw in more economic growth, they also pull resources from government coffers, and they may commit governments to future funding for public services that benefit the incentivized businesses. The authors use a panel of 32 states and data from 1990 to 2015 to understand how incentives affect states' fiscal health. They find that after controlling for the governmental, political, economic, and demographic characteristics of states, incentives draw resources away from states. Ultimately, the results show that financial incentives negatively affect the overall fiscal health of states.